"Fake News" and Cyber-Propaganda in Sub-Saharan Africa: Recentering the Research Agenda. Issue 4 (2nd October 2019) - Mare, Admire; Mabweazara, Hayes Mawindi; Moyo, Dumusani
ABSTRACT: Dominant narratives about the contemporary problem of "fake news" and cyber-propaganda have focused on how its evolution and manifestation has been closely linked with the rise of populist politics, digital capitalism, the transformation of the public sphere and structural weaknesses of liberal and mainstream media. These narratives often use the Western gaze as an analytical and theoretical toolkit to understand a global phenomenon, thereby missing local specificities and nuances. In this special issue we argue that any attempt to make sense of the evolution, mutation and sharing of fake news and cyber-propaganda in sub-Saharan Africa cannot be done outside the determining and constraining context of the production and consumption of news in Africa. At the core of this context of production and consumption are resource-constrained newsrooms, an ever-shifting communication ecology, realignment of the relationship between producers and consumers of content, digitization of political communication, media repression, digital literacy and competencies and competing regimes of truth and non-truth. The special issue engages with the phenomena of "fake news" and cyber-propaganda in sub-Saharan Africa. It attempts to show that there are alternative ways of thinking about the normative and epistemological challenges facing both journalism and society, more generally, in the twenty-first century. The issue carries six theoretically driven empirical studies that use a wide range of qualitative evidence to closely explore a number of themes, including the production and consumption of "fake news" and cyber-propaganda in specific contexts within the continent.